Controlled Glioma Cell Migration and Confinement Using Biomimetic‐Patterned Hydrogels. Issue 1 (25th November 2021) - Oh, EunBi; Meckes, Brian; Chang, Jinyoung; Shin, Donghoon; Mirkin, Chad A.
Abstract : Cancer cell migration is significantly influenced by the physical properties (e.g., mechanics, topography) of the local extracellular matrix (ECM). However, how cells guide their movement in a complex, heterogeneous landscape while interpreting various physical factors, especially those with sizes on the subcellular length scale, is not completely understood. Herein, a photodegradable hydrogel is fabricated with control over the spatial distribution of features with different physical characteristics. On the surface of this hydrogel, patterns of features with sizes and spacings on the subcellular to cellular length scale are generated using a digital micromirror device, and the influence of the organization of these patterns on cellular migratory behavior is investigated. The size and spatial arrangement of hard (or stiff) and soft domains, more so than their topography, is found to have a significant impact on the migration speed. Using this approach, the maximum migration speed is observed on hydrogels with 10 μm pattern sizes spaced 10 μm apart. In this regime, the cells are confined and interact with both hard and soft regions at their periphery. Together, this study of cell–ECM interactions at the interface of hard and soft domains provides insights into how cancer cells interact with their environment. Abstract : Using hydrogel surfaces with photopatterned local stiffness and topographical heterogeneities, cancer cell migration and responsiveness to subcellular mechanical heterogeneity is investigated. Cells seeded on hydrogels preferentially confine to stiffer regions while moving on the surface. The migration rate reaches peak speeds when geometric spacing of the mechanical domains reaches critical dimensions commensurate with the cell size.